Organizational and methodological aspects of the internal control of products processing (World of finance, 2019)
Introduction. Control is one of the principle functions in the management system. Every decision-making, including planning and budgeting, should be controlled. The control consequences emerge as some information about disclosure of violations and some difficulties in managerial decisions fulfillment. In the general management process control appears as an element of correction retraction and it is carried out by the functional control system.Purpose. The internal control system has to maintain special information receiving which characterizes quantitative and qualitative indicators of processing enterprise activities; the effectiveness of resources using involved in the production processes of certain business and business processes. It concerns not only problems monitoring at work and personnel punishment for their divagations, it is also closely connected with management targets regarding staff work efficiency control. Internal control involves a wide range of activity depending on the aim: from ordinary amendments at the subdivision level to radical changing demands, the whole mechanism restructuring of activities in order to solve economic problems. The essence of internal control, as well as its subjects and objects in terms of measures, relating to the process of acquisition, production and products sale, can be discovered only by taking into account the industry specifics, techniques and arrangements for processing enterprises economy.Results. Such foreign and native economists as I. Bielobzhetskyi, M. Bilukha, F. Butynets, V. Derii, M. Kuzhelnyi, M. Chumachenko and Ye. Kaliuha in their scientific works research the problems of the control system mostly at the level of the whole country. However, it would be reasonable to form the organization and methodology for the internal control system at agricultural processing enterprises considering the sector specific nature. The common problem in the organization of the internal control system, specific for processing enterprises, is the lack of special units control, whereas these functions are performed mostly by accountants. Another problem to be solved is the discrepancy between control procedures technology and control purposes.Conclusions. Thus, we consider the internal control organization as its direct arrangement and improvement of the methodology and techniques in order to save property.